Consumer behaviour of halal logo food online purchasing during Covid-19 pandemic: the role of spirituality, reputation, trust and satisfaction - Sharifah Roziah, Syed Mahzan (2022)
Pandemic of Covid-19 makes online purchasing of all business companies towards their consumers are extremely important. In this research, it all about the consumers behaviours when they are going online to purchase halal food products mainly among the Muslims in the period of virus pandemic. Currently, the pandemic is causing various problems that arise from the aspects of business and consumers management. Among them is about face-to-face purchases can no longer be done due to the high risk of infection. So, the opportunity to buy online becomes an option. And then, it is important to research how the related factors that influence the consumers behaviours such as spirituality, reputation, trust, and satisfaction. This research uses a quantitative method by conducting an online survey of consumers at two universities in northern Malaysia. A total of 196 respondents was responded to the online questionnaires. The results revealed that spirituality, trust, reputation, and satisfaction have positive relationship on halal logo food purchasing among the consumers during the pandemic of Covid-19. These findings have demonstrated how important the online purchasing that need to be enhanced by companies in food industry to meet their consumer’s demand. Perhaps the same approach can be further designed to cater international consumers’ demand mainly among millions of Muslims in China, Indonesia, Russia, and middle east countries.